Pengaruh Gaya Kepemimpinan, Komitmen Organisasi dan Motivasi Kerja Terhadap Kinerja Perusahaan - Sartika, Ni Kadek Putri; Wijana Asmara Putra, I Nym (E-Jurnal Akuntansi; Vol 29 No 2 (2019)DO - 10.24843/EJA.2019.v29.i02.p23, 2019)
This research was conducted at PT. Prosperous Indobali Trada all branches in Bali. Data collection is done by questionnaire with saturated sampling technique. The number of employees who become respondents is as many as 46 people. Data Analysis Method used in this research is to use multiple linear regression analysis. Based on the results of the analysis found Leadership Style has a positive and significant effect on company performance. This shows that the greater the leadership style the company will increase. Positive and significant organizational commitment to the company's performance. This shows the higher level of organizational commitment, the higher the company will be. Positive and significant work motivation on company performance. This shows the higher level of work motivation, the higher the increase in the company. Keywords : Leadership Style; Organizational Commitment; Motivation; Performance.